Pharmacovigilance of carbamazepine at the Marta Abreu Polyclinic. Santa Clara, 2022 - Adrián Ruíz López (Medisur)
Background: in practice, the term narcotic is applied to pharmaceutical specialties that contain active ingredients that act on the central nervous system, modifying it, and to master formulas with the same active ingredients. Objective: to characterize clinically and epidemiologically the patients who consume carbamazepine in a health area of the Santa Clara municipality. Methods: descriptive, cross-sectional study in patients consuming carbamazepine, belonging to the Marta Abreu Teaching Polyclinic, from January the 1st, 2021 to April the 1st, 2022. 209 patients were included and the following variables were measured: age, sex, number of patients according to diagnoses, number of patients according to new protocols and time of consumption of the treatment. Results: the age group from 51 to 60 predominated with 43 patients (20.5%), within this group the female sex (11.0% of the total); the predominant diagnosis was generalized epilepsy with a total of 93 patients. The female sex predominated with a total of 59 patients and in them the largest number of expired files was found, with a total of 16. According to new protocols, patients with a diagnosis of trigeminal, glossopharyngeal or facial neuralgia (7 patients) predominated. Regarding the time of consumption, patients with the same diagnosis as the previous ones and behavioral disorder due to a medical illness predominated, both groups with treatments of up to three years. Conclusions: knowledge about the use and abuse of narcotic drugs is important, as well as keeping all health personnel updated to achieve optimal control over these substances.